Additive manufacturing of WC-Co cermets using composite powders - Al-Thamir, Mohaimen Habeeb Makki (2021)
Cermets are defined as “Composite materials consisting of two constituents, one being either an oxide, carbide, boride, or similar inorganic compound, and the other a metallic binder”. Cermets based on tungsten carbide -cobalt (WC-Co), in both sintered and coatings forms, are extensively used in the fabrication of engineering components that require excellent wear resistance. The excellent wear properties of sintered cutting tools arise because WC-Co cermets give a compromise between toughness, provided by the metal matrix (Co), and the hardness of the ceramic (WC) phase. However, in overlay coatings, a reaction between WC and Co during deposition can degrade their wear performance from the ideal one of WC in a ductile Co matrix. Additive manufacturing (AM) technologies such as laser powder bed fusion (L-PBF) or laser direct energy deposition (DED-L) can provide significant design flexibility in the manufacture of cutting tools. However, there are significant challenges in processing WC-Co materials when melting of the Co binder phase is involved. The effect of process parameters needs to be fully understood and optimised to avoid cracks, pores, and excessive reaction between the WC and Co phases during manufacture. In the present study, a novel type of WCM-12 wt.% Co powder, prepared by a “satelliting” method, was employed in both L-PBF and DED-L studies; WCM represents the commercially available mixed carbide with the tradename Spherotene®. In addition, a commercially available plasma densified WC-Co feedstock with a smaller particle size and higher Co (17 wt.%) content was also examined in the L-PBF process. In this study and for the first time, it is now possible to produce applicable WC-Co feedstock for AM using the simple manually prepared satelliting method. In DED-L, single clads were fabricated. The results demonstrated stable depositions, uniform distribution of WCM particles in the matrix, good bonding with the substrate, and an almost full density matrix. These aspects can show the applicability of this feedstock to produce high quality coatings. To define an appropriate process map, two hypothesises were employed. The first one compromised between linear energy density and powder feed rate. The second one used effective energy density versus powder deposition density. The results showed that the second approach is more representative to the melt pool physics. Also, a high WCM dissolution increased the microhardness and wear resistance of the multitrack deposited coatings. In L-PBF, the processability of the satellited WCM-12 wt.% Co feedstock was investigated. Melting trials were undertaken to evaluate the consolidation behaviour of single tracks within a single layer. Also, the evolution of surface morphology of single layers and multilayers was studied. A continuous and relatively uniform single-track morphology was obtained. This has led to a relatively smooth single layer without cracks or matrix pores. However, increasing the numbers of layers increased cracks significantly. The plasma densified WC-17 wt.% Co powder was used in a different L-PBF machine of a relatively large laser spot size. Uniform cubic samples without distortions were fabricated in a process window. However, all samples revealed microcracks and open pores on the as-laser-scanned surfaces.